Case Report: A case of thoracoscopic mediastinal tumor resection in a child with ROHHAD syndrome - Ma, Yangwei; Gao, Jia; Huo, Lianghong; Wang, Fang (Frontiers in Pediatrics, 2024)
Rapid-onset obesity with hypoventilation, hypothalamic dysfunction, and autonomic dysregulation (ROHHAD) is an exceptionally rare condition. This case report highlights a child diagnosed with ROHHAD syndrome, presenting with a mediastinal tumor. ROHHAD syndrome is characterized by early onset obesity, hypothalamic dysfunction, autonomic dysfunction, inadequate ventilation, suspected seizures, and abnormal behavior. The presence of a mediastinal tumor necessitated surgical intervention. Key considerations during surgery included hypernatremia due to hypothalamic dysfunction, potential airway challenges, preoperative anemia, and hemodynamic fluctuations during the removal of the sizable mediastinal tumor.Comprehensive preparations ensured a safe operation. Notably, some children with this syndrome may exhibit symptoms such as decreased gastrointestinal function, polyuria, and thermoregulatory disturbances.Vigilance is essential during anesthesia assessment in these patients.Anesthesiologists should enhance their knowledge of this condition and tailor their management strategies based on individual clinical presentations and the specific planned surgical procedures.